Implementing Text File Data Security Using Super Encryption (Affine Cipher Algorithm and OTP) - Imay Kurniawan; Purwadi Budi Santoso; Anung (Universitas Insan Cendekia Mandiri, 2026)
Data security is a crucial aspect, especially for confidential, personal, or strategic information. Threats such as eavesdropping and data manipulation by unauthorized parties require a robust protection system. The purpose of this research is to develop a model or application that integrates Affine Cipher and OTP for data protection and to determine the computational performance of a combined implementation of both algorithms. The cryptographic algorithm method uses super-encryption, a combination of the Affine Cipher and OTP algorithms. The resulting encryption produces ciphertext that is difficult to crack because the key length is equal to the message length and the key is generated randomly. The combination of the two algorithms was successfully implemented using the super-encryption method. Affine Cipher acts as an initial substitution layer, while OTP provides a random layer that ensures high-level confidentiality. The use of OTP effectively overcomes the main weakness of Affine Cipher against frequency analysis.